2002
DOI: 10.1093/fampra/19.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of guided written disclosure of stressful experiences on clinic visits and symptoms in frequent clinic attenders

Abstract: The findings extend previous findings to frequent clinic users, using a new form of written disclosure aimed at shifting trauma from implicit to explicit memory. The GDP may be an inexpensive additional intervention in primary care for reducing symptoms and clinic visits among frequent clinic users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 32 publications
2
62
0
Order By: Relevance
“…In the therapeutic environment, there is also opportunity for therapist feedback and guidance on writing sessions, which can increase cognitive processing and enhance benefits. For example, a guided written disclosure intervention (in which participants were instructed to describe a traumatic event chronologically, reflect on their thoughts and feelings at the time of the event and how it affected their life, and then to describe their current perspective on it) resulted in reduced symptoms and fewer clinic visits, compared to control writing, in a sample of frequent clinic attenders (Gidron et al, 2002). Guided instruction in written or verbal disclosure can help facilitate shifts in how people process a traumatic experience such as HIV or AIDS diagnosis, which can have an impact on changes in their lives, their emotional adjustment, and their health.…”
Section: Discussionmentioning
confidence: 99%
“…In the therapeutic environment, there is also opportunity for therapist feedback and guidance on writing sessions, which can increase cognitive processing and enhance benefits. For example, a guided written disclosure intervention (in which participants were instructed to describe a traumatic event chronologically, reflect on their thoughts and feelings at the time of the event and how it affected their life, and then to describe their current perspective on it) resulted in reduced symptoms and fewer clinic visits, compared to control writing, in a sample of frequent clinic attenders (Gidron et al, 2002). Guided instruction in written or verbal disclosure can help facilitate shifts in how people process a traumatic experience such as HIV or AIDS diagnosis, which can have an impact on changes in their lives, their emotional adjustment, and their health.…”
Section: Discussionmentioning
confidence: 99%
“…2 A systematic review indicated that frequent attenders are highly heterogeneous, and have high rates of physical disease, psychiatric illness, and social difficulty. 3 One group of intervention studies with frequent attenders focused on characteristics associated with frequent attendance, such as psychosocial factors, including depression, 4,5 somatisation, 6 stressful experiences, 7 or widowhood; 8 or physical factors such as chronic bronchitis, 9 or diabetes. 10 A common underlying assumption is that if health problems are improved, the need to consult decreases, although findings to support this have been both negative 4,5 and positive.…”
Section: Introductionmentioning
confidence: 99%
“…10 A common underlying assumption is that if health problems are improved, the need to consult decreases, although findings to support this have been both negative 4,5 and positive. [6][7][8][9][10] Another group of intervention studies [11][12][13][14][15][16] used a comprehensive focus with multi-component interventions, although results were inconclusive, and the interventions tended to be unsuccessful; also, most of these studies had methodological problems. O'Dowd intervened successfully in 'heartsink' patients, most of whom are frequent attenders, although no control group was involved.…”
Section: Introductionmentioning
confidence: 99%
“…It would seem that writing about traumatic experiences might be a useful intervention for reducing such symptoms, but empirical results have been mixed. While some researchers have found health benefits of writing about trauma among frequent healthcare users (Gidron et al, 2002), other researchers (Batten, Follette, Hall, & Palm, 2002;Freyd, Klest, & Allard, 2005) have found no overall benefit of writing about traumatic experiences. Studies that have focused specifically on the impact of writing about trauma in people who report experiencing significant trauma such as sexual assault, or other betrayal or life-threat traumas (e.g., Batten et al, 2002, Freyd et al, 2005 have found no benefit of writing about trauma.…”
Section: Introductionmentioning
confidence: 99%